Normal levels of plasmatic and red cells cholinesterase - Siqueira, Maria Elisa Pereira Bastos de; Fernícola, Nilda Alícia Gallego Gándara de; Borges, Eustáquio Linhares (Revista de Saúde Pública, 1978)
The plasmatic and red cell cholinesterase was determined in 57 individuals aged 18-37 years, all students from the University of S. Paulo (Brazil). In order to know the normal mean values, two methods were used: Michel's and Caraway's. Through Michel's method a mean value of 0.83 deltapH/h was found for red cells cholinesterase and 1.11 deltapH/h for plasmatic cholinesterase. Through Caraway's method the mean value obtained was 77 U.